An agribusiness perspective of demonetization in central region of the state of Gujarat in India - Ritambhara Singh; Mahesh R. Prajapati (Journal of Economic Structures, 2020)
This paper aims at understanding the effect of demonetization announced in November 2016 on agribusiness subsystems, its effect on consumer purchasing criteria, and the problems that surfaced in rural areas to move towards digitalization. This research was exploratory in nature and so adopted an open-ended approach through interviews of 200 farmers selected from 20 villages of two districts; one economically progressive and the other economically backward, in central region of the state of Gujarat in India. Besides, 50 landless farm laborers, 12 input dealers, 20 wholesalers, 20 retailers, 4 each of processors, exporters, and logistic service providers operating in study area were also interviewed. The focus group discussions were also conducted. Secondary data were gathered from various government sources. Exploratory factor analysis was conducted to examine the consumer purchasing criteria. Garrett's ranking technique was used to find the problems of moving to digital transaction. The production activity slowed down due to immediate cash crunch. Agriculture also suffered a setback. Socio-economic factors contributed strongly to the consumer purchasing criteria post-demonetization. The rural economy worked on local credit basis during the demoneti-zation period. Delayed sowing was observed due to non-availability of inputs during initial days of announcement of demonetization. Farm labor suffered losses. Prices of perishables crashed. More bank accounts opened in rural area as dairy payments were made mandatory through electronic mode only. Infrastructural bottlenecks, complex e-banking language and lack of technical knowhow, etc., posed problems before the rural economy to go digital. Strong policy interventions were suggested to make digitalization more popular in rural areas. Removal of infrastructural bottlenecks was suggested to absorb the shock effects of announcements like demonetization.
Keywords: 330; Demonetization; Agribusiness; Consumer purchasing criteria; Gujarat; India; Digitalization